Penerapan Fengshui Aliran Bentuk pada Interior Kantor âXâ - Grace Mulyono, Melissa Megasari Walujo (Intra, 2014)
The application of Fengshuipatternflow of Company âXâ is a research which examining and understanding the theory of Fengshui, integrated with interior design as theart of organizing space. This study is conducted by comparing current field report with the existing literatures, then analyzed whether the real life condition is relevant to the theoretical background ither based on Fengshuior interior design point of view. This paper discusses about Fengshui and interior design as two disciplines which used for arranging the space and benefitting for open up the perception regarding to Fengshui as one of the culture that can be applied on setting up a room especially the interior of the office room. Both knowledge has different orientation, yet on the application, all of them canbeused for thepurpose of achieving the optimum result related to the productivityÂ  of the workers inside the office. From the analysis, it can be concluded that Company âXâ have been 80% accordant to the Fengshui and interior design theory.